Y5U multilayer ceramic capacitors with high-specific capacitance and low-equivalent series resistance - Ochi, A (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 1991)
A dielectric powder material, for Y5U multilayer ceramic capacitors was developed in the Pb(Mg(1/3)Nb(2/3))O (3)-Pb(Ni(1/3)Nb(2/3))O(3)-PbTiO (3) ternary system by using an alkoxide process. Multilayer ceramic chip capacitors (10 muF) with high specific capacitances were fabricated using this powder. A Ag80%-Pd20% alloy was used for the internal electrodes. The alkoxide-derived capacitor had an extremely high specific capacitance of about 500 muF/cm(3) and a small temperature dependence meeting Y5U specifications of the EIA standard. The equivalent series resistance was approximately 20 mOmega at 500 kHz. The breakdown voltages of the capacitor were 300 V or higher. In accelerated load life tests and load humidity tests, no degradation of insulation resistance was found during 1000 h of testing